Enhancing lightweight block cipher algorithm OLBCA through decreasing cost factor - Al-Dabbagh, Sufyan Salim Mahmood; Alshaikhli, Imad Fakhri Taha; Al-Enezi, Khalid Abdulkareem; Alyaqoup, Mohammed Jasem (Institute of Electrical and Electronics Engineers Inc., 2016)
Lightweight block cipher algorithms are vital for constrained environment. There are three factors should be considered when you design lightweight block cipher algorithm which are security, performance and cost. In this paper, we have improved the cost factor of OLBCA algorithm by decreasing the number of Substitution box (S-box) without a major effect on other factors. Also, we have applied three attacks, which are differential, integral and boomerang attacks. From the result, it can be seen that our proposed algorithm has less cost than other algorithms and still secured.